The management of remains payable in the federal universities in the context of Decree No. 9,428/2018 - Mota, Samuel Cavalcante; Corrêa, Denise Maria Moreira Chagas; Nascimento, Roberto Sérgio do (Contextus - Revista Contemporânea de Economia e Gestão, 2022)
The study used indicators of RP management and statistical tools to identify the impact of Decree no. 9,428/20218 on the RP management of federal universities. The results indicate that: Decree No. 9,428/2018 did not significantly impact the settlement of RP in federal universities; the significant cancellation of RP in 2019 may not have been caused, by the lack of a deadline for execution, but by the limitation of the performance of federal universities in the settlement of RP capital expenditures e; the COVID-19 pandemic may have increased the number of commitments on RP for other current expenditures.